Leveling the playing field between large and small institutions: Evidence from the SEC’s XBRL mandate - BHATTACHARYA, Nilabhra (Institutional Knowledge at Singapore Management University, 2018)
We investigate how XBRL adoption affects smaller institutions’ access to financial statement information relative to their larger counterparts. We examine three aspects of trading responsiveness: abnormal trading volume, response speed to 10-K information, and decision to trade immediately following the 10-K filing. With regard to all three aspects of trading responsiveness, we find that small institutions’ responsiveness to 10-K news increases significantly more relative to the change experienced by large institutions from the pre- to post-XBRL periods. We further document that small institutions’ stock picking skills in the 10-K filing period increase more compared to those of large institutions following the regulation. Our results are robust to a battery of falsification and sensitivity tests. Collectively, our results suggest that the informational playing field between small and large institutions has become more even following the SEC’s XBRL mandate.